Intoxicação por Ateleia glazioviana (Leg.-Papilionoideae) em bovinos - Gava, Aldo (2000)
A chronic disease affecting cattle from the west of the state of Santa Catarina and northwest of the state of Rio Grande do Sul, Brazil, is described. The disease occurs mainly during the fall and winter and affects cattle over one-year-old. It is characterized by sudden death or death preceded by clinical signs of congestive heart failure, which include subcutaneous dependant edema and engorged and pulsating jugular vein. The cases of congestive heart failure may be or not associated with clinical signs of lethargy and blindness. Morbidity rates are 10-60% and mortality may be up to 95%. Gross lesions include discrete pale and firm areas in the myocardium, mainly along the coronary vessels and extending into to the septum. In cattle with congestive heart failure the liver is enlarged and has a nutmeg appearance. Histopathological changes include swelling and necrosis of cardiac myofibers and interstitial fibrosis and macrophagic infiltrate. The livers of cattle with congestive heart failure have centrolobular congestion occasionally associated with fatty change and fibrosis. The white matter of the brain of cattle with clinical signs of lethargy shows spongy degeneration (status spongiosis). The disease was reproduced in calves by feeding the leaves of Ateleia glazioviana. Clinical presentation of lethargy was reproduced with single doses of 40 g/kg and with dairy doses of 2.5, 5.0, 7.5, and 10.0 g/kg. Chronic myocardial lesions were reproduced with daily doses 2.5, 5.0, and 7.5 g/kg administrated for long periods of time and with multiple doses starting up with 1g/kg and consistently increasing 1g/kg/day until 15g/kg day totaling 120g/kg.